Determinants of firm exit and growth in the food processing sector: Evidence from Ghana - Andam, Kwaw S.; Asante, Seth (2018)
We explore the determinants of firm exit and growth in the food processing sector using nationally representative data for 745 firms in Ghana. In our sample, 168 of the firms exited the sector during the period 2014-2017. Firms were more likely to exit if they were in a rural district, were younger, and were involved in grain milling, but there was little impact of firm size on the likelihood of exit. In terms of firm growth, we find that tax registration, combined with registration with the national food regulator, had positive impacts on firm growth, while tax registration alone has a weaker effect. Therefore, for the food processing sector, efforts to promote formalization of firms for tax purposes would yield greater benefits if firms are also encouraged to undergo regulatory inspections and certification.